Wage Premium and Master’s Degrees: Some Empirical Evidence from Spain - Caparrós-Ruiz, Antonio (Emerald Insight, 2023)
The current expansion of the knowledge economy and its requirements of highly educated workers make interesting to analyse the effects on the labour market outcomes of completing a master’s degree. This study examines the factors determining the probability of pursuing a postgraduate programme, and observes whether workers reaching this educational attainment reap the benefits of their human capital investment through better paid jobs compared to college-only degree holders. On the other hand, it analyses whether individuals with a master’s degree are more prone to upward wage mobility. The study relies on data obtained from the second Survey on the Labour Insertion of University Graduates conducted by INE (2019). This survey allows us to observe labour market transitions of the first group of Spanish university graduates under the European Higher Education Area and their earnings. The methodological procedure consists of the estimation of wage models controlling for the unobservable differences between workers who have or have not completed a master’s degree. The results indicate a significant positive impact of master’s degree on salaries. Furthermore, individuals with postgraduate studies are more prone to upward wage mobility in comparison to college-only degree holders. The econometric specification applied allows us to compute the direct effect of a master’s degree on wages, and predict the average probability that an individual is in a determined wage interval according to the knowledge area and controlling by the rest of characteristics. The findings are helpful to diagnose and understand how the knowledge acquired through postgraduate studies are rewarded by the labour market, which is essential to evaluate the return on educational investments when making decisions about whether or not to continue postgraduate studies. This research addresses novelty aspects on tertiary education in Spain and its effects on workers’ careers.
This research is a pre-print version of the article titled "Wage Premium and Master's Degrees: Some Empirical Evidence from Spain" published by the review International Journal of Manpower Vol. 44 Issue 8.
Keywords: Licenciados universitarios - Trabajo; Knowledge Economy; Labour Market; Master’s Degree; Wage